Phenotypic and genetic spectrum of alveolar capillary dysplasia: a retrospective cohort study. Issue 4 (22nd October 2019) - Jourdan-Voyen, Laurélia; Touraine, Renaud; Masutti, Jean-Pierre; Busa, Tiffany; Vincent-Delorme, Catherine; Dreyfus, Lelia; Molin, Arnaud; Savey, Baptiste; Mounzer, Abraham; Assaf, Ziad; Atallah, Veronique; da Cruz, Vanessa; et al.
Abstract : Objective: Alveolar capillary dysplasia (ACD) is one of the causes of pulmonary hypertension. Its diagnosis is histological but new pathogenetic data have emerged. The aim of this study was to describe a French cohort of patients with ACD to improve the comprehension and the diagnosis of this pathology which is probably underdiagnosed. Methods: A retrospective observational study was conducted in French hospitals. Patients born between 2005 and 2017, whose biological samples were sent to the French genetic reference centres, were included. Clinical, histological and genetic data were retrospectively collected. Results: We presented a series of 21 patients. The mean of postmenstrual age at birth was 37.6 weeks. The first symptoms appeared on the median of 2.5 hours. Pulmonary hypertension was diagnosed in 20 patients out of 21. Two cases had prolonged survival (3.3 and 14 months). Histological analysis was done on lung tissue from autopsy (57.1% of cases) or from percutaneous biopsy (28.6%). FOXF1 was found abnormal in 15 patients (71.4%): 8 deletions and 7 point mutations. Two deletions were found by chromosomal microarray. Conclusion: This study is one of the largest clinically described series in literature. It seems crucial to integrate genetics early into diagnostic support. We propose a diagnostic algorithm for helping medical teams to improve diagnosis of this pathology.